POLITIK KORUPSI : Kendala Sistemik Pemberantasan Korupsi di Indonesia - PUJI ASTUTI, PUJI ASTUTI (Politika: Jurnal Ilmu Politik, 2011)
AbstractCorruption is a phenomenon that always arise in a variety of reports. Especially these dayswhen politicians become suspect of corruption and fled to neighboring countries. SBY's governmentcommitted to combating corruption, but until the second period of his leadership has not shownencouraging results. Corruption became so difficult to eradicate. Even corruption that caused so muchsuffering to the people, not to be used as a common enemy. Systemic corruption committed indeedbe an obstacle for efforts to eradicate corruption in Indonesia. Systemic corruption is actuallypoliticize of corruption which is practicing with strategy to make your higher official feel comfortableand subordinate to enjoy. Systemic corruption is what causes the corruptor being untouchable.Moreover, corruption also involves a number of law enforcement official like policse, prosecutors andjudgdes, even justice of the supreme court. But the most difficult part is the emergence of thepermissive attitude of society towards corruption. Therefore the handling of corruption also requires asystemic way,including the revitalization of ethical standards.Keywords: Corruption, Political Corruption, Revitalization of Ethical StandardsA. PENDAHULUAN